Examination of the Etiologic Causes in Patients Presenting with Elevated Parathormone - İdris Kırhan; Mehmet Ali Eren (Galenos Yayinevi, 2019)
Objective:Parathyroid hormone (PTH) levels are elevated in the blood due to various reasons and named as primary or secondary hyperparathyroidism. There is no any study that investigated the etiology of elevated PTH.Materials and Methods:The study included 137 patients who had elevated PTH, which was detected in blood tests that were performed due to any reason, during 1-year period.Results:Of all patients 118 (86.1%) were female and 19 (13.9%) were male. Vitamin D deficiency was found in 88 (64.2%), primary hyperparathyroidism (PHPT) in 38 (27.7%), familial hypocalciuric hypercalcemia (FHH) in 8 (5.8%), and chronic renal failure (CRF) in 3 (2.2%) patients.Conclusion:Vitamin D deficiency is a common disorder in general population, and occasionally coexisted with increased PTH level. Therefore, vitamin D deficiency should be kept in mind when PTH studied as a first test and is found to be high. The other reason such as PHPT, FHH and CRF must be also investigated.